(untitled) (Proceedings of Voronezh State University. Series: Geology, 2018)
Mercury toxicity is becoming an increasingly complex problem as a result of global contamination of near-surface deposits by heavy metals. It was found that mercury concentrations in the underlying rocks ≤ 10 mg/kg stimulate plant growth in height, root length, ability to branch rice, increase yield. Concentrations of Hg2+ 100 mg/kg negatively affect the growth of true leaves. Mercury is predominantly deposited in leaves and rice grains. As sources of mercury supply to near-surface deposits within Vietnam, agrarian technologies, the consequences of military operations, are singled out.